Foliar elementary sulfur assimilation by soybean - Vitti, Godofredo Cesar (2007)
The objective of this work was to evaluate the elementary sulfur (S0) assimilation applied on soybean leaves, and its efficiency compared to the fertilization done in the soil, according to the dose and nature of the nutrient source. The S0 applied to leaves, independently of the dose and source, was assimilated by the plant, what resulted in increase of total protein content in the leaf. All S sources applied to leaves increased the grain yield, similarly to the application to the soil. The same productivity was observed with the use of 20 kg ha-1 of S0 in the soil or 6 kg ha-1 applied to leaves. The elementary S application efficiency on leaves, based on the content of total soluble protein, was superior to application efficiency on soil.